Gastric Yield Pressure and Gastric Yield Volume to Assess Anti-Reflux Barrier in a Porcine Model. (10th April 2013) - Duarte, Marcos E. S.; Freitag, Carmen P. F.; Fornari, Fernando; Kruel, Cleber R. P.; Sanches, Paulo R. S.; Thomé, Paulo R. O.; Callegari-Jacques, Sidia M.; Möllerke, Roseli O.; Vicente, Yvone A. M. V. A.; Goldani, Helena A. S.; Barros, Sérgio G. S.
ABSTRACT Anti-reflux barrier (ARB) resistance may be useful to test new treatments for gastroesophageal reflux (GER). The ARB has been estimated by increasing gastric yield pressure (GYP) and gastric yield volume (GYV) in animal models but has not been validated. This study aimed to develop an experimental model suitable for assessing the ARB resistance to increasing intragastric pressure and volume and its reproducibility in a seven-day interval. Ten two-month-old female Large-White swine were studied. Intragastric pressure and volume were recorded using a digital system connected to a Foley catheter inserted through gastrostomy into the stomach. GYP and GYV were defined as the gastric pressure and volume able to yield gastric contents into the esophagus detected by esophageal pH. A sudden pH drop below 3 sustained during 5 min was considered diagnostic for gastric yield. Animals were studied again after seven days. On days 0 and 7, there were no significant differences for GYP (mean ± SD = 7.66 ± 3.02 mmHg vs. 7.07 ± 3.54 mmHg, p = .686) and GYV (636.70 ± 216.74 ml vs. 608.30 ± 276.66 ml; p = .299), respectively. Concordance correlation coefficient (ρc) was significant for GYP (ρc = 0.634, 95% CI = 0.141–0.829, p = .006), but not for GYV (ρc = 0.291, 95% CI = −0.118 to 0.774, p = .196). This study demonstrated an experimental model, assessing the ARB resistance. GYP seems to be a more reliable parameter than GYV for assessment of ARB resistance.